Stress analysis of mechanical seal in API 610 pump / Balqis Erizy Zainal - Balqis Erizy , Zainal (2021)
This research project uses Ansys Finite Element Analysis software to conduct Stress Analysis of Mechanical Seal used in API 610 pump. Maximum Sealing Pressure will be applied as per API682 requirement and maximum and minimum stress will be monitored. The finite element method has become a powerful tool for the numerical solutions of a wide range of engineering problems. Besides equivalent stress, strain and deformation of the mechanical seals will also be analyzed. The modeling of the mechanical seal was done by Ansys Design Modeler and the analysis was performed by using Ansys workbench 2021 R1 version. In the model, the mechanical seal face parts are going to be in contact and the remaining parts like ring and steel support not combined. At the end of research, we will be able to select the best candidate for the critical part of mechanical seal in API 610, which is the sleeve part.